In-situ Polymerization of Styrene to Produce Polystyrene / Montmorillonite Nanocomposites - Lahouari Mrah; Rachid Megabar; Mohammed Belbachir (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
A reactive cationic surfactant cetyltrimethylammonium bromide (CTAB) was synthesized for intercalation of montmorillonite Mmt, a Maghnite type of clay. The pristine montmorillonite (Mmt) was obtained from Algerian plant with a cation exchange, Organophilic Mmt, was prepared by ion exchange between Na+ ions in the clay. CTAB-intercalated Mmt particles were easily dispersed and swollen in styrene monomer, PS/Mmt-CTAB nanocomposites were synthesized via in-situ polymerization, in-situ polymerization, this method is based on the swelling of the silicate layers with the liquid polymer. The polymer composites were characterized using different techniques such as X-ray diffraction (XRD), The results were showed that, the basal space of the silicate layer increased, as determined by XRD, from 12.79 to 32.603 Å. Transmission electron microscopy (TEM) indicated that exfoliation of Mmt was achieved. In this current research, thermal gravimetric analysis (TGA) and  force atomic microscopy (AFM) were also studied. Copyright © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).